Lectotype designations in Acmaeodera Eschscholtz and Anthaxia Eschscholtz, and new synonymy in Phaenops Dejean and Anthaxia (Coleoptera: Buprestidae) - Westcott, Richard L.; Bílý, Svatopluk (Zootaxa, 2018)
Lectotype designations are provided for Acmaeodera conoidea Fall, 1899, A. recticollis Fall, 1899, Anthaxia (Haplanthaxia) sculptipennis Obenberger, 1924, and A. (H.) oneili Obenberger, 1931. The following new synonymy is proposed: Phaenops caseyi (Obenberger, 1944), syn. nov. = P. lecontei (Obenberger, 1928), Phaenops horni (Obenberger, 1944), syn. nov. = P. fulvoguttata (Harris, 1829), and Anthaxia (Haplanthaxia) oneili Obenberger, 1931, syn. nov. = A. (H.) sculptipennis Obenberger, 1924).